2022
DOI: 10.1099/ijsem.0.005243
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of Rhizobiaceae revisited: proposal of a new framework for genus delimitation

Abstract: The alphaproteobacterial family Rhizobiaceae is highly diverse, with 168 species with validly published names classified into 17 genera with validly published names. Most named genera in this family are delineated based on genomic relatedness and phylogenetic relationships, but some historically named genera show inconsistent distribution and phylogenetic breadth. The most problematic is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(71 citation statements)
references
References 78 publications
4
65
2
Order By: Relevance
“…In 2020, a study performed phenotypic, genomic, and phylogenetic analyses of the genus Ensifer and suggested that the genus should be separated into two genera, one for the symbiotic clade and the other for the nonsymbiotic clade [ 185 ]. More recently, a publication on the IJSEM suggested the revision of family Rhizobiaceae [ 186 ]. The extensive study suggests a threshold for core-proteome average amino acid identity (cpAAI) of approximately 86% as a new framework for genus delimitation.…”
Section: Rhizobia Study Casementioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, a study performed phenotypic, genomic, and phylogenetic analyses of the genus Ensifer and suggested that the genus should be separated into two genera, one for the symbiotic clade and the other for the nonsymbiotic clade [ 185 ]. More recently, a publication on the IJSEM suggested the revision of family Rhizobiaceae [ 186 ]. The extensive study suggests a threshold for core-proteome average amino acid identity (cpAAI) of approximately 86% as a new framework for genus delimitation.…”
Section: Rhizobia Study Casementioning
confidence: 99%
“…It is noteworthy to mention that cpAAI must not be used as sole information for genus delimitation, and the authors specify “approximately 86%” to provide some flexibility regarding the evolution of each genus. Although not yet updated in the LPSN website as validated names, among the reclassifications based on the study of Kuzmanović and collaborators [ 186 ], there are arguments that the unification of the genera Ensifer and Sinorhizobium is no longer justified, and eight new combinations were suggested, but not all involving rhizobial strains [ 186 ].…”
Section: Rhizobia Study Casementioning
confidence: 99%
“…The core-proteome average amino acid identity (cpAAI) between the isolate TH2 and reference Rhizobiaceae spp. was <76% (Table S4), which was below the threshold of ~86% for delimitation of Rhizobiaceae genera proposed recently ( 37 ). This suggested that isolate TH2 represents a new genus and species, described here as Onobrychidicola muellerharveyae gen. nov. sp.…”
Section: Resultsmentioning
confidence: 57%
“…The cpAAI between the isolate TH2 and reference Rhizobiaceae spp. were <76 % (Table S4), which was below the threshold of ~86 % for delimitation of Rhizobiaceae genera proposed recently [60]. This suggested that isolate TH2 represents a new genus and species, described here as Onobrychidicola muellerharveyae gen. nov sp.…”
Section: Core-genome Phylogeny Overall Genome Relatedness Indices And...mentioning
confidence: 57%